MSME Perceptions towards Internet Use: A Comparison of Before and During the COVID-19 Outbreak in Indonesia - Luthfina Ariyani; Wati Hermawati; Rahmi Lestari Helmi; Ishelina Rosaira; Andi Budiansyah (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This paper aims to identify and compare MSME perceptions on Internet use in their business processes before and during the COVID-19 outbreak in Indonesia. Design/Methodology/Approach: This study employs a web-based survey involving 464 respondents from across MSME owners in Indonesia. A paired sample t-test was used to compare the perception which was delineated under the technology, organisation, environment (TOE) framework. Research findings: The results show significant changes in the Internet use among 464 MSMEs “before” and “during” the COVID-19 outbreak. Overall, we categorised the perception into three groups, namely (1) positive before the COVID-19 outbreak, (2) positive amid the COVID-19 outbreak, and (3) negative for both before, and amid the COVID-19 outbreak. Theoretical contribution/Originality: This study seeks to extend the theory of technology adoption, and its intended use, by understanding the phenomena from a different point of view, by identifying how the MSME’s perceptions of technology changed during the presence of the COVID-19 outbreak, by comparing aspects of the Internet adoption on the conditions before, and during the pandemic. Practitioner/Policy implication: This study suggests future strategies to encourage better Internet adoption and use among MSMEs based on the three aforementioned categories. Research limitation/Implications: Further research may address much more on the adoption variables, and consider more geographic distributions of the samples. Keywords: Technology Adoption, TOE Framework, Internet, MSME, COVID-19 JEL Classification: O32